Tolerance of melon cultivars to irrigation water salinity - Francisco A. de L. Pereira; José F. de Medeiros; Hans R. Gheyi; Nildo da S. Dias; Welka Preston; Cybelle B. e L. Vasconcelos (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The use of saline water for irrigation causes severe restriction to nutritional balance, growth and production in many crops due to the effect of salts on plant and soil. The objective of this study was to investigate the response of melon (Cucumis melo L.) cultivars to various levels of irrigation water salinity on yield and fruit quality. A field experiment was conducted in a split-plot randomized block design with four replicates. The factors were five levels of irrigation water salinity (0.54, 1.48, 2.02, 3.03 and 3.90 dS m-1) in the plots and five melon cultivars (C1 - Sancho - Pele de sapo; C2 - Medellín - Pele de sapo; C3 - Mandacaru - Canary; C4 - Néctar - Galia; C5 - Sedna - Cantaloupe) in the sub-plots. According to the results, among the five genotypes studied, Sancho was the most salt-tolerant genotype, followed by Mandacaru, Medellín, Sedna and Néctar. Since irrigation water salinity did not influence the mean fruit weight, the reduction in the number of fruits was the main cause of yield reduction of the melon crop under high salinity water. The contents of total soluble solids increased under high salinity level.